The THO/TREX Complex Component RAE2/TEX1 Is Involved in the Regulation of Aluminum Resistance and Low Phosphate Response in Arabidopsis - Zhu, Yi-Fang; Guo, Jinliang; Zhang, Yang; Huang, Chao-Feng (Frontiers in Plant Science, 2021)
The C2H2-type zinc finger transcription factor SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) plays a critical role in aluminum (Al) resistance and low phosphate (Pi) response mainly through controlling promoting the expression of the malate transporter-encoding gene ARABIDOPSIS THALIANA ALUMINUM ACTIVATED MALATE TRANSPORTER 1 (AtALMT1). We previously showed that REGULATION OF ATALMT1 EXPRESSION 3 (RAE3/HPR1), a core component of the THO/TREX complex, is involved in the regulation of nucleocytoplasmic STOP1 mRNA export to modulate Al resistance and low Pi response. Here, we report that RAE2/TEX1, another core component of the THO/TREX complex, is also involved in the regulation of Al resistance and low Pi response. Mutation of RAE2/TEX1 reduced the expression of STOP1-downstream genes, including AtALMT1. rae2/tex1 was less sensitive to Al than rae3/hpr1, which was consistent with less amount of malate secreted from rae3/hpr1 roots than from rae2/tex1 roots. Nevertheless, low Pi response was impaired more in rae2/tex1 than rae3/hpr1, suggesting that RAE2/TEX1 also regulates AtALMT1-independent pathway to modulate low Pi response. Furthermore, unlike RAE3/HPR1 that regulates STOP1 mRNA export, mutating RAE2/TEX1 did not affect STOP1 mRNA accumulation in the nucleus, although STOP1 protein level was reduced in rae2/tex1. Introduction of rae1 mutation into rae2/tex1 mutant background could partially recover the deficient phenotypes of rae2/tex1. Together, our results demonstrate that RAE2/TEX1 and RAE3/HPR1 play overlapping but distinct roles in the modulation of Al resistance and low Pi response.